War or health? a reader - Taipale, Ilkka (2002)
This comprehensive reader of 70 specially commissioned essays provides an unusually wide-ranging examination of the connection between warfare and human health and society. Contributors look at the changing character of wars and their effects on civilization, the medical and health aspects of different types of weapons, the changing roles of health professionals in war. the arms trade, social tensions, the media, theories of violence, and war as a social institution.